Tinjauan Yuridis Proses Perekrutan Dan Pemilihan Calon Anggota Komisioner Komisi Pemberantasan Tindak Pidana Korupsi (KPK) - I Nyoman Yudhi Astika; I Nyoman Putu Budiartha; I Made Minggu Widyantara (Jurnal Analogi Hukum, 2022)
KPK commissioners are appointed through a recruitment process involving the executive (President) and the legislature (DPR). The mechanism for selecting KPK candidates tends to be political. Furthermore, the following issues will be discussed: (1) how is the recruitment system for KPK members, (2) how is the selection process for the leadership of the corruption eradication commission (KPK) according to Law Number 19 of 2019 concerning the Corruption Eradication Commission. The type of research used in the thesis is normative research. The sources of legal materials used are Primary Legal Materials, Secondary Legal Materials, Tertiary Legal Materials. Techniques for obtaining legal materials used are document studies, literature studies, internet studies. Analysis of legal materials used is descriptive data analysis method. And the conclusion of the thesis is the Corruption Eradication Commission Member Recruitment System In the Corruption Eradication Commission Law, the appointment of KPK commissioners goes through several stages of the recruitment process which is carried out with a technical selection approach. The level of selection of the commissioners of the Corruption Eradication Commission based on the NRI Law No. 19/2019 regarding the Corruption Eradication Commission.